METTL3/N6‐methyladenosine/ miR‐21‐5p promotes obstructive renal fibrosis by regulating inflammation through SPRY1/ERK/NF‐κB pathway activation. Issue 16 (24th June 2021) - Liu, Erpeng; Lv, Lei; Zhan, Yonghao; Ma, Yuan; Feng, Jinjin; He, Yulin; Wen, Yibo; Zhang, Yanping; Pu, Qingsong; Ji, Fengping; Yang, Xinghuan; Wen, Jian Guo
Abstract: Renal fibrosis induced by urinary tract obstruction is a common clinical occurrence; however, effective treatment is lacking, and a deeper understanding of the mechanism of renal fibrosis is needed. Previous studies have revealed that miR‐21 impacts liver and lung fibrosis progression by activating the SPRY1/ERK/NF‐kB signalling pathway. However, whether miR‐21 mediates obstructive renal fibrosis through the same signalling pathway has not been determined. Additionally, studies have shown that N6‐methyladenosine (m 6 A) modification‐dependent primary microRNA (pri‐microRNA) processing is essential for maturation of microRNAs, but its role in the maturation of miR‐21 in obstructive renal fibrosis has not yet been investigated in detail. To address these issues, we employed a mouse model of unilateral ureteral obstruction (UUO) in which the left ureters were ligated for 3, 7 and 14 days to simulate the fibrotic process. In vitro, human renal proximal tubular epithelial (HK‐2) cells were transfected with plasmids containing the corresponding sequence of METTL3, miR‐21‐5p mimic or miR‐21‐5p inhibitor. We found that the levels of miR‐21‐5p and m 6 A modification in the UUO model groups increased significantly, and as predicted, the SPRY1/ERK/NF‐kB pathway was activated by miR‐21‐5p, confirming that miR‐21‐5p plays an important role in obstructive renal fibrosis by enhancing inflammation. METTL3 was found to play a major catalytic role in m 6 A modification in UUO mice and drove obstructive renal fibrosis development by promoting miR‐21‐5p maturation. Our research is the first to demonstrate the role of the METTL3‐m 6 A‐miR‐21‐5p‐SPRY1/ERK/NF‐kB axis in obstructive renal fibrosis and provides a deeper understanding of renal fibrosis.